The effect of short‐term exercise prehabilitation on skeletal muscle protein synthesis and atrophy during bed rest in older men. Issue 1 (21st December 2020) - Smeuninx, Benoit; Elhassan, Yasir S.; Manolopoulos, Konstantinos N.; Sapey, Elizabeth; Rushton, Alison B.; Edwards, Sophie J.; Morgan, Paul T.; Philp, Andrew; Brook, Matthew S.; Gharahdaghi, Nima; Smith, Kenneth; Atherton, Philip J.; et al.
Abstract: Background: Poor recovery from periods of disuse accelerates age‐related muscle loss, predisposing individuals to the development of secondary adverse health outcomes. Exercise prior to disuse (prehabilitation) may prevent muscle deterioration during subsequent unloading. The present study aimed to investigate the effect of short‐term resistance exercise training (RET) prehabilitation on muscle morphology and regulatory mechanisms during 5 days of bed rest in older men. Methods: Ten healthy older men aged 65–80 years underwent four bouts of high‐volume unilateral leg RET over 7 days prior to 5 days of inpatient bed rest. Physical activity and step‐count were monitored over the course of RET prehabilitation and bed rest, whilst dietary intake was recorded throughout. Prior to and following bed rest, quadriceps cross‐sectional area (CSA), and hormone/lipid profiles were determined. Serial muscle biopsies and dual‐stable isotope tracers were used to determine integrated myofibrillar protein synthesis (iMyoPS) over RET prehabilitation and bed rest phases, and acute postabsorptive and postprandial myofibrillar protein synthesis (aMyoPS) rates at the end of bed rest. Results: During bed rest, daily step‐count and light and moderate physical activity time decreased, whilst sedentary time increased when compared with habitual levels ( P  < 0.001 for all). Dietary protein and fibre intake during bed rest were lower than habitual values ( P  < 0.01 for both). iMyoPS rates were significantly greater in the exercised leg (EX) compared with the non‐exercised control leg (CTL) over prehabilitation (1.76 ± 0.37%/day vs. 1.36 ± 0.18%/day, respectively; P  = 0.007). iMyoPS rates decreased similarly in EX and CTL during bed rest (CTL, 1.07 ± 0.22%/day; EX, 1.30 ± 0.38%/day; P  = 0.037 and 0.002, respectively). Postprandial aMyoPS rates increased above postabsorptive values in EX only ( P  = 0.018), with no difference in delta postprandial aMyoPS stimulation between legs. Quadriceps CSA at 40%, 60%, and 80% of muscle length decreased significantly in EX and CTL over bed rest (0.69%, 3.5%, and 2.8%, respectively; P  < 0.01 for all), with no differences between legs. No differences in fibre‐type CSA were observed between legs or with bed rest. Plasma insulin and serum lipids did not change with bed rest. Conclusions: Short‐term resistance exercise prehabilitation augmented iMyoPS rates in older men but did not offset the relative decline in iMyoPS and muscle mass during bed rest.